Proceedings of the 51st ACM Southeast Conference 2013
DOI: 10.1145/2498328.2500083
|View full text |Cite
|
Sign up to set email alerts
|

Review spam detector with rating consistency check

Abstract: Nowadays it is very common for people to write online reviews of products they have purchased. These reviews are a very important source of information for the potential customers before deciding to purchase a product. Consequently, websites containing customer reviews are becoming targets of opinion spam. --undeserving positive or negative reviews; reviews that reviewers never use the product, but is written with an agenda in mind. This paper aims to detect spam reviews by users. Characteristics of the review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 11 publications
0
16
0
1
Order By: Relevance
“…A burst pattern may not be a good indicator to judge the spam, as a user may be writing reviews for many products. In [30], the authors used temporal based rating-consistency to detect spam and marked abnormally frequent reviewers as spammers. In [31], the authors criticized the temporal approach and considered it unuseful as spammer may post fewer reviews.…”
Section: Related Workmentioning
confidence: 99%
“…A burst pattern may not be a good indicator to judge the spam, as a user may be writing reviews for many products. In [30], the authors used temporal based rating-consistency to detect spam and marked abnormally frequent reviewers as spammers. In [31], the authors criticized the temporal approach and considered it unuseful as spammer may post fewer reviews.…”
Section: Related Workmentioning
confidence: 99%
“…Opinion and sentiment analysis of reviews extract and aggregate positive and negative opinions from product reviews [5]. Researchers study the problem of generating feature-based summ aries of customer reviews of products sold online.…”
Section: It Related Workmentioning
confidence: 99%
“…Given a data set of customer reviews of any particular product, the task involves three subtasks: (1) identifying features of product that customers have discussed or expressed their opinion on. (2) For each feature, identifYing review sentences which gives an opinion (positive or negative) and (3) producing a summary using the discovered information [5].…”
Section: It Related Workmentioning
confidence: 99%
“…Second, users' sentiment expressed in reviews should be precisely identified. Although reviews contain the information of star ratings, the ratings and actual emotions may not be totally consistent [21], [22]. For example, one user may write positive feedback like "Great", but only give one-star rating.…”
Section: Introductionmentioning
confidence: 99%